The Management of Extracurricular Marching Band Instruction: A Case Study of the Gema Dirgantara Marching Band at SMP Negeri 3 Kroya - Agit Bagus Hartadi; Bagus Susetyo (Jurnal Ragam Pengabdian, 2026)
Marching band extracurricular activities in schools function as a music learning process that requires systematic management of rehearsal and performance activities. However, in practice, the management of marching band activities is often oriented primarily toward performance outcomes, resulting in less attention being given to the learning aspects. This study aims to describe the management of rehearsal and performance activities as a music learning process in the Gema Dirgantara marching band extracurricular program at SMP Negeri 3 Kroya. The study employed a descriptive qualitative approach, with data collected through observations, interviews, and documentation involving the instructor, the person in charge of the program, and students. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing, while data credibility was ensured through source triangulation. The results show that the management of rehearsal and performance activities is implemented through integrated management functions, namely planning, organizing, implementation, and evaluation. Rehearsal and performance activities are designed as a unified learning process, with performances positioned as authentic assessments of learning outcomes.